If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t = 3t + -4 Reorder the terms: 5t = -4 + 3t Solving 5t = -4 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 5t + -3t = -4 + 3t + -3t Combine like terms: 5t + -3t = 2t 2t = -4 + 3t + -3t Combine like terms: 3t + -3t = 0 2t = -4 + 0 2t = -4 Divide each side by '2'. t = -2 Simplifying t = -2
| 3+8(x)=3(2)(x)-1 | | 150=-16t^2+118t+3 | | 1/2a-4=3-1/4 | | 7+.2(x-1)=5+.3(x-1) | | 4/5×5 | | (16-9i)-(2-9i)= | | 3/5x-1/10x=x-15/2 | | 9p+4+3p= | | 2y-6.3=y+13 | | 28+28+28= | | 5/8*2/5 | | 5(t+3)= | | 12-2x=8(x)+4 | | 40+40+40= | | 492x+10=5x+3x+9 | | 3n+4n-5+3= | | -4y-2=3y-4 | | 2y+40=7y | | -216=-9g | | 2(9y-7)=14 | | c-3=12 | | r=2xy-3p | | 45-6x=x+171 | | 0.6+k=1.67 | | X*4x=12.6 | | 1/3÷3 | | (4x+2)+(7x+4)+(3x+20)=180 | | 2(2x+8)=2(4x+8) | | D=125.145h | | 9x-6x+1=9x+1-x | | 8b+8b+4b=-12 | | 2-2x=2x+2 |